Preoperative elevation of serum C - reactive protein is predictive for prognosis in myeloma bone disease after surgery - Zahlten-Hinguranage, Anita; Goldschmidt, Hartmut; Cremer, Friedrich Walter; Egerer, Gerlinde; Möhler, Thomas; Witte, D; Bernd, Ludger; Sabo, Desiderius; Zeifang, Felix (British journal of cancer, 2006)
We investigated whether preoperative levels of serum C-reactive protein (CRP) and its correlation with tumour clinicopathological findings adds prognostic information beyond the time of diagnosis in patients with myeloma bone disease (MM) to facilitate the surgical decision-making process. Six hundred and fifty-eight myeloma patients were evaluated retrospectively for surgery. Clinicopathological variables of patients who underwent surgery (n=71) were compared between patients with preoperative CRP ⩾6 mg l−1 and those with CRP <6 mg l−1. Univariate and multivariate analyses were performed to identify prognostic factors after surgery. Patients with an increase of CRP prior to surgery showed inferior survival compared to patients with normal levels. Patients with normal CRP levels at diagnosis but elevations prior to surgery do seem to have a similar unfavourable overall survival (OS) than patients with an increase both, at diagnosis and at surgery. Conversely, patients with normal CRP levels prior to surgery still have the best OS, irrespective of their basic values. Multivariate analysis revealed preoperative CRP levels above 6 mg l−1 Lactate dehydrogenase (LDH) above normal, and osteolyses in long weight bearing bones as independent predictors of survival. These findings suggest that in patients with MM serum levels of CRP increase during disease activity and might be significantly correlated with specific disease characteristics including adverse prognostic features such as osteolyses in long weight bearing bones. Thus, preoperative elevated CRP serum levels might be considered as independent predictor of prognosis and could provide additional prognostic information for the risk stratification before surgical treatment in patients with myeloma bone disease.